2022
DOI: 10.5430/wje.v12n3p17
|View full text |Cite
|
Sign up to set email alerts
|

Teachers and Participatory Action Research for Developing Learning Environments

Abstract: This research aims to develop learning environments through Participatory Action Research (PAR) methodology in a specific context of the Department of Electronics, Nong Han Industrial and Community Education College. Three development outcomes are expected: (1) changes in expected and non-expected outcomes of action; (2) action-based learning in the researchers, research participants and the institute and (3) knowledge from the grounded theory. The results are as the followings: 1) there are positive changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…(Sanrattana, 2018). This belief is confirmed by the research of Uttamadhammo and Phrakrusutheejariyawattana (2021), Thawinwong and Sanrattana (2022), and Soipimai and Sanrattana (2023) that focus on research by review literature from articles available on the Internet, including the same PAR methodology was used.…”
Section: Introductionmentioning
confidence: 78%
“…(Sanrattana, 2018). This belief is confirmed by the research of Uttamadhammo and Phrakrusutheejariyawattana (2021), Thawinwong and Sanrattana (2022), and Soipimai and Sanrattana (2023) that focus on research by review literature from articles available on the Internet, including the same PAR methodology was used.…”
Section: Introductionmentioning
confidence: 78%
“…For example, the research on "Collaborative Practices to Empower Teachers' Capacities for the 21st Century" by Soipimai and Sanrattana (2023), "Cooperative Practices to Enhance the Quality of Work Integrated Learning. at Nong Khai Technical College" of Sarapoom and Phrakrudhammapissamai (2021), "Development of Learning by E-Learning System: A Case of Mahamakut Buddhist University, Mahavajiralongkorn Rajaviyalaya Campus" of Uttamadhammo and Phrakrusutheejariyawattana (2021), "Participatory Practice "Teach Less, Learn More": A Case of Srikranuanwittayakom School" by Rooptam and Sanrattana (2021), "Practicing Collaborative Teachers to Strengthen Student's Visionary Leadership Skills" by Poonvichaen and Sutheejariyawat (2022), and "Teachers and Participatory Action Research for Developing Learning Environments" by Thawinwong and Sanrattana (2022).…”
Section: Resultsmentioning
confidence: 99%
“…This research is corroborated by other researchers who used similar propulsion in their research. For example, the research on "Cooperative Practices to Enhance the Quality of Work Integrated Learning at Nong Khai Technical College" of Sarapoom and Phrakrudhammapissamai (2021), "Participatory Practice "Teach Less, Learn More": A Case of Srikranuanwittayakom School" by Rooptam and Sanrattana (2021), "Practicing Collaborative Teachers to Strengthen Student's Visionary Leadership Skills" by Poonvichaen and Sutheejariyawat (2022), "Teachers and Participatory Action Research for Developing Learning Environments" by Thawinwong and Sanrattana (2022), "Collaborative Practices to Empower Teachers' Capacities for the 21st Century" by Soipimai and Sanrattana (2023), and "Development of Learning by E-Learning System: A Case of Mahamakut Buddhist University, Mahavajiralongkorn Rajaviyalaya Campus" of Uttamadhammo and Phrakrusutheejariyawattana (2021). Therefore, it is suggested that the Participatory Action Research (PAR) methodology involves research, management, development, and problem-solving activities that take place all at the same time.…”
Section: Discussion and Suggestionsmentioning
confidence: 99%